HARMONIOUS DEVELOPMENT OF THE GENERATION AND THEIR KNOWLEDGE IS THE BASIS OF THE PROGRESS OF UZBEKISTAN - Kurbanova Malika Hayitovna (Galaxy International Interdisciplinary Research Journal, 2021)
It is difficult to achieve success in the development of our country without raising human morale. A spiritually free and free people can achieve great things in any field due to deep and complete thinking. In other words, only a spiritually healthy, strong society can be ready for reform. This article discusses the harmonious development of the generation and the fact that their knowledge is the basis of the development of Uzbekistan.